Coaching from the sidelines: the nuclear periphery in genome regulation - Buchwalter, Abigail (Nat Rev Genet, 2019)
The genome is packaged and organized nonrandomly within the 3D space of the nucleus to promote efficient gene expression and to faithfully maintain silencing of heterochromatin. The genome is enclosed within the nucleus by the nuclear envelope membrane, which contains a set of proteins that actively participate in chromatin organization and gene regulation. Technological advances are providing views of genome organization at unprecedented resolution and are beginning to reveal the ways that cells co-opt the structures of the nuclear periphery for nuclear organization and gene regulation. These genome regulatory roles of proteins of the nuclear periphery have important influences on development, disease and ageing.